2009
DOI: 10.1016/j.nima.2009.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Development of thick-foil and fine-pitch GEMs with a laser etching technique

Abstract: We have produced thick-foil and fine-pitch gas electron multipliers (GEMs) using a laser etching technique. To improve production yield we have employed a new material, Liquid Crystal Polymer, instead of polyimide as an insulator layer. The effective gain of the thick-foil GEM with a hole pitch of 140 µm, a hole diameter of 70 µm, and a thickness of 100 µm reached a value of 10 4 at an applied voltage of 720 V. The measured effective gain of the thick-foil and fine-pitch GEM (80 µm pitch, 40 µm diameter, and 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 20 publications
0
38
0
Order By: Relevance
“…23 is cross-section through a mechanically drilled, one mm thick fiberglass sheet with 300 mm holes at one mm pitch [52]. Other groups have developed technologies to produce hole patterns on a variety of supports [53][54][55][56][57].…”
Section: Manufacturing Of Gem Electrodesmentioning
confidence: 99%
“…23 is cross-section through a mechanically drilled, one mm thick fiberglass sheet with 300 mm holes at one mm pitch [52]. Other groups have developed technologies to produce hole patterns on a variety of supports [53][54][55][56][57].…”
Section: Manufacturing Of Gem Electrodesmentioning
confidence: 99%
“…Ionization electrons created along the photoelectron track drift with a constant velocity in a uniform electric field between the drift electrode and the micro-pattern Gas Electron Multiplier (GEM). 20,21 Drifted charge is then amplified in the GEM holes, and collected on the read-out strips located beneath the GEM. Two-dimensional images of photoelectron tracks are formed from a one-dimensional strip readout using the strip location and arrival time multiplied by the drift velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 shows the setup for the test described in §3. 3 not a vacuum sealed chamber, we selected Ar/CO 2 (70%/30%) gas mixture, with which many GEM studies have been done. 3 We confirmed that the gain variability did not change with gas, although the absolute value of gain changed.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
“…3 not a vacuum sealed chamber, we selected Ar/CO 2 (70%/30%) gas mixture, with which many GEM studies have been done. 3 We confirmed that the gain variability did not change with gas, although the absolute value of gain changed. Note that the gas was continuously flowing in this test, so the detector pressure followed the ambient environment.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation